الأحاديث التي سكت عنها الحاكم والذهبي معا في الجزأين الأخرين للمستدرك وتلخيصه : دراسة نقدية - ياما، فايلة
This study deals with Imam al-Hakim's book al-Mustadrak in which the author collected the Prophetic traditions fulfilling the combined criteria of al-Bukhari and Muslim or those one of them, but were not narrated by them. Accordingly, it was incumbent upon al-Hakim to only mention in his book those traditions that satisfy the said criteria. However, he included in it traditions that were not transmitted according to those criteria. He even was so tolerant in validating traditions that Imam al-Dhahabi felt urged to criticize his judgements on traditions and to point out his indulgences in his book Talkhis al-Mustadrak. Yet, despite the great job done he left many traditions, which he did, not dealt with. This study is an attempt to carry on and complete the work started by Imam al-Dhahabi. The researcher has surveyed all the traditions included in the last two volumes (another student took the first two volumes) of al-Mustadrak on which both al-Hakim and al-Dhahabi kept silent. Then, she traced them in other sources of hadith and judged them based on the views of scholars concerning their degrees of authenticity. In the case of traditions on which no such views are available, the researcher ventured to decide on the authenticity of those traditions by examining their transmission chains and contents. The researcher found that the number of traditions under consideration in the two volumes she studied is 209 hadiths of varying degrees of authenticity. They include al-sahih, al-hasan, al-da'if, and very few al-mawdu. Most of the traditions on which al-Hakim kept silent were actually narrated as supportive material (shawahid and mutaba'at) to those constituting the essential material (usul) in chapters of the book. The researcher reached the conclusion that al-Hakim and al-Dhahabi mostly kept silent on certain traditions not out of forgetfulness, but for one of the following two reasons. That, if a tradition is mentioned more than once, both scholars would simply decides on its status when it first occurs. Or, if a tradition contains in its chain of transmission one narrator whose name has been mentioned in a preceding tradition whose status has been decided, then al- Hakim and al-Dhahabi would not feel the need to deal with it again.